Cytoplasmic intron retention, function, splicing, and the sentinel RNA hypothesis. (4th November 2013) - Buckley, Peter T.; Khaladkar, Mugdha; Kim, Junhyong; Eberwine, James
<x xml:space="preserve">Abstract</x> Cytoplasmic splicing represents a newly emerging level of transcriptional regulation adding to the molecular diversity of mammalian cells. As examples of this noncanonical form of transcript processing are discovered, the evidence of its importance to normal cellular function grows. Work from a number of groups using a variety of cell types is steadily identifying a large number of transcripts (and soon to be even larger as genome‐wide analyses of retained introns across a number of cellular phenotypes are currently underway) that undergo some level of regulated endogenous extranuclear splicing as part of their normal biosynthetic pathway. Here, we review the existing data covering cytoplasmic retained intron sequences and suggest that such sequences may be a component of 'sentinel RNA' that serves to generate transcript variants within the cytoplasm as well as a source for RNA‐based secondary messages. WIREs RNA 2014, 5:223–230. doi: 10.1002/wrna.1203 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.